If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -1y = 96 Solving X + -1y = 96 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add 'y' to each side of the equation. X + -1y + y = 96 + y Combine like terms: -1y + y = 0 X + 0 = 96 + y X = 96 + y Simplifying X = 96 + y
| 10x^2-3x=8 | | 8(-8x-7)=6(-10x-6) | | 4(8+x)=-(8+2x)-8 | | 4+5p=60 | | -5x-7=-9-3x | | 2x-7=-8+3x | | 8a+12=a | | x^5+4=0 | | -4(7-7x)=-6(1-x)-176 | | a+2b=-7 | | 2(9-x)=5(x-7)-3 | | 6(8-3x)=-(-2x-8)-20 | | 49+(10-5)=54 | | 6(8-3)=-(-2x-8)-20 | | (n-2)=360 | | 10a^2+5ab+5a= | | -242=-9(10+x) | | 9(7x-5)=-9(6x-7)-342 | | 22x+3=2 | | 4(2.5x-2)=(5x-5)+2 | | 2c-a=bc+1 | | 4ab+6a= | | 3x(2x+3)= | | 22x+3=128 | | 5(6+5x)=161+2(-8x-4) | | (4-8i)(3+i)=0 | | 5(6x+5x)=161+2(-8x-4) | | 1x+2=y | | 5(6+5x)=161+2(-8-4) | | 0.25x+0.15(100-x)=19 | | 3abs(x+4)=8 | | 6(x-9)=-4(x-5) |